Околдованная: роман / Бертрис Смолл - Смолл Бертрис (АСТ, 2007)
Экземпляры: ф.23 (20201111) / Инвентарный номер: 60472 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: С 51 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44